Slope Risk Assessment from Geospatial Data - Zainal Arifin, Nur Ilyana (Universiti Teknologi PETRONAS, 2017)
Slope risk assessment is important in any projects to avoid any danger occurrences that could lead to deaths and fatalities such as landslide. Generally, the slope risk assessment is done on site by taking the elevation and contour data for slope stability analysis. There are two common methods in determining the slope risk which are finite element method and limit equilibrium method. However, both methods required to obtained data on site which consume time and money. More time and money would be spent if the site is further from the workplace. Therefore, the slope risk assessment method through geospatial analysis might be the solution for this problem. LiDAR is an effective way to obtained data. LiDAR uses remote sensing to obtain data without going to the site. Some studies have even shown that LiDAR is the most precise data and there are many case studies have been conducted based on LiDAR data. The analysis of the slope risk assessment can be conducted from LiDAR data in ArcGIS in spatial analytics. In this project, the area covered is at Cameron Highlands.